Experimental habitat fragmentation disrupts host–parasite interaction over decades via life‐cycle bottlenecks. Issue 9 (16th June 2022) - Bitters, Matthew E.; Meyers, Jacqui; Resasco, Julian; Sarre, Stephen D.; Tuff, Kika T.; Davies, Kendi F.
Abstract: Habitat loss and fragmentation are likely to seriously impact parasites, a less studied but critical component of ecosystems, yet we lack long‐term experimental evidence. Parasites structure communities, increase connectivity in food webs, and account for a large proportion of an ecosystem's total biomass. Food web models predict that parasites with multiple obligate hosts are at greater risk of extinction because the local extinction, or reduction in abundance, of any host will result in a life‐cycle bottleneck for the parasite. We examine the response of a parasite and its multiple hosts to forest fragmentation over 26 years in the Wog Wog Habitat Fragmentation Experiment in southeastern Australia. The parasite is the nematode Hedruris wogwogensis, its intermediate host is the amphipod, Arcitalitrus sylvaticus, and its definitive host is the skink, Lampropholis guichenoti . In the first decade after fragmentation, nematodes completely disappeared from the matrix (plantation forestry) and all but disappeared from their definitive host (skinks) in fragments, and by the third decade after fragmentation had not appreciably recovered anywhere in the fragmented landscape compared to continuous forest. The low prevalence of the nematode in the fragmented landscape was associated with the low abundance of one or the other host in different decades: low abundance of the intermediate host (amphipod) in the first decade and low abundance of the definitive host (skink) in the third decade. In turn, the low abundance of each host was associated with changes to the abiotic environment over time due largely to the dynamically changing matrix as the plantation trees grew. Our study provides rare long‐term experimental evidence of how disturbance can cause local extinction in parasites with life cycles dependent on more than one host species through population bottlenecks at any life stage. Mismatches in the abundance of multiple hosts over time are likely to be common following disturbance, thus causing parasites with complex life cycles to be particularly susceptible to habitat fragmentation and other disturbances. The integrity of food webs, communities, and ecosystems in fragmented landscapes may be more compromised than presently appreciated due to the sensitivity of parasites to habitat fragmentation.